Effects of the Addition of Calcium Acetate into Silicate-Based Electrolytes on the Properties of MAO Coatings Produced on Zirconium (vol 129, pg 504, 2016) [Correction] - Cengiz, S.; Azakli, Y.; Yazici, M.; Gayretli, B.; Gencer, Y.; Tarakci, M. (Polish Acad Sciences Inst Physics, 2017)
…